Strategi Pelayanan Kantor Kementerian Agama Kota Panyabungan - Hasfin Ansori; Abdur Rozak; Efrika Noviyanti Lase; Ika Sahriani; Fazilah Fazilah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Vertical agencies of the Ministry of Religion are agencies within the Ministry of Religion that carry out the duties and functions of the Ministry of Religion in the regions. The vertical agencies of the Ministry of Religion consist of regional offices of the provincial Ministry of Religion and district/city offices of the Ministry of Religion. Ministry of Religion office services are activities carried out by an organization or agency in order to meet the needs of the community. A strategy in service is needed to improve service quality. The strategies implemented include: Increasing service innovation by utilizing online media, providing computers in the sub-district area to assist the service process, providing direction and socializing the community to be administratively orderly by being good within the scope of service.